Juridical Analysis of the Regulation of Hospital Operational Termination Due to Legal Violations - T.Kusuma; B.Santoso (International Medical Journal Corp. Ltd, 2026)
Introduction: Hospitals play a critical role in public health, but legal violations require strict regulatory enforcement, including operational termination. This study addresses the regulatory framework and legal consequences of halting hospital operations due to statutory breaches. Methods: This study utilizes a normative juridical research method, analyzing statutory provisions, legal doctrines, and case law related to medical law and administrative enforcement. Results: The findings reveal that while the government possesses the authority to terminate hospital operations, the current legal framework suffers from overlapping jurisdictions, vague enforcement criteria, and a lack of standardized procedural safeguards. Discussion: The discussion highlights a significant conflict between the administrative necessity of penalizing non-compliant institutions and the constitutional right of citizens to access uninterrupted healthcare. A comprehensive literature review emphasizes that proportional enforcement mechanisms must integrate alternative dispute resolutions and gradual sanctions before resorting to total closure, thereby filling the existing gap between public administrative law and medical ethics. Conclusions: This study concludes that the regulatory framework requires immediate harmonization to balance legal enforcement with public health continuity. It is recommended that policymakers establish a specialized, independent medical regulatory tribunal and draft clear, tiered administrative guidelines to ensure that operational termination remains a measure of last resort.